2008
DOI: 10.1089/gte.2008.0009
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Familial Mediterranean Fever Gene Mutations in 202 Patients with Familial Mediterranean Fever

Abstract: In our patients, we defined 21 different genotypes of MEFV gene and the most common mutation was M694V. The most common symptoms were abdominal pain and fever. We detected significant correlation between the M694V, E148Q, and V726A mutations and clinical findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
6
16
2
1
Order By: Relevance
“…In the studies by Touitou et al (4) and the Turkish FMF study group (15), the most common MEFV mutations in Turkey were M694V (57 and 51.4%, respectively), followed by M680I (16.5 and 14.4%, respectively) and V726A (13.9 and 8.6%, respectively). M694V was the most common mutation in our study, similarly to many previous studies (17,(19)(20)(21)(22)(23)(24). We found that M694V (41.3%) accounted for the majority of FMF chromosomes, followed by E148Q (19.9%), M680I (10.3%), V726A (7.2%), P369S (3.06%), K695R (2.6%), M694I (2.2%), R761H (3.06%), A744S (0.76%), and F479L (0.38%) ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the studies by Touitou et al (4) and the Turkish FMF study group (15), the most common MEFV mutations in Turkey were M694V (57 and 51.4%, respectively), followed by M680I (16.5 and 14.4%, respectively) and V726A (13.9 and 8.6%, respectively). M694V was the most common mutation in our study, similarly to many previous studies (17,(19)(20)(21)(22)(23)(24). We found that M694V (41.3%) accounted for the majority of FMF chromosomes, followed by E148Q (19.9%), M680I (10.3%), V726A (7.2%), P369S (3.06%), K695R (2.6%), M694I (2.2%), R761H (3.06%), A744S (0.76%), and F479L (0.38%) ( Table 1).…”
Section: Discussionsupporting
confidence: 92%
“…We found that M694V (41.3%) accounted for the majority of FMF chromosomes, followed by E148Q (19.9%), M680I (10.3%), V726A (7.2%), P369S (3.06%), K695R (2.6%), M694I (2.2%), R761H (3.06%), A744S (0.76%), and F479L (0.38%) ( Table 1). The frequencies of E148Q mutation have been reported to range from 3.5% to 18.3% in Turkey (13,20). We also detected a high incidence of E148Q mutation (19.9%).…”
Section: Discussionsupporting
confidence: 60%
“…In the previous studies from Turkey, the frequency of E148Q mutation was found to range between 1.36 and 30.8%. In agreement with our study, it was found as the second most commonly seen mutation in many studies from Turkey (Akin et al, 2010;Dogan et al, 2012;Etem, 2010;Gulec et al, 2012;Ozturk et al, 2008;Pasa et al, 2008;Solak et al, 2008;Ulgenalp, 2009), whereas it was found as the most commonly seen mutation in the study by Evliyaoglu et al (2009) and by Yesilada et al (2012), with allele frequencies of 30.8% and 10.38%, respectively. E148Q mutation was the third most commonly observed mutation in the study by Ceylan et al (2012) and by Dundar et al (2011) with the allele frequencies of 4.42 and 5.15%, respectively.…”
Section: Discussionsupporting
confidence: 91%
“…55,56 Several studies describe p.Glu148Gln as a disease-causing mutation. [57][58][59][60][61][62] The Infevers Web site also lists it as causing disease-related symptoms. Other studies have not found p.Glu148Gln to be associated with clinical disease and have, therefore, considered it a benign polymorphism.…”
Section: Genotype-phenotype Correlationsmentioning
confidence: 99%